Absence of Morphological Case and Gender Marking in Contemporary Hasidic Yiddish Worldwide. Issue 2 (June 2022) - Belk, Zoë; Kahn, Lily; Szendrői, Kriszta Eszter
Abstract : This paper demonstrates that the language of the post-War generations of adult Haredi (that is, strictly Orthodox), primarily Hasidic, speakers of Yiddish in the major Hasidic centers worldwide lacks morphological case and gender. Elicited spoken and written data from native Haredi speakers of Yiddish from Israel and the United States, aged 18–87, and limited additional evidence from Canada and Belgium, reveal a complete absence of distinction between masculine, feminine, and neuter genders as well as between the nominative, accusative, and dative cases. While some speakers make use of a variety of morphological definite determiner and attributive adjective forms, their use is not determined by case or gender distinctions. Most of the speakers in our study have an invariable determiner pronounced as /dɛ/ or /di/, whereas the earlier case and gender suffixes on attributive adjectives have been reanalyzed as a single attributive marker, /ɛ/. These findings are consistent with our previous work on the loss of case and gender in the Hasidic Yiddish of London's Stamford Hill and support our proposal that the Yiddish spoken in (primarily Hasidic) Haredi communities can be considered a distinct variety of the language known as Contemporary Hasidic Yiddish.*